1994
DOI: 10.1016/0161-5890(94)90001-9
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the antibody molecule

Abstract: The structures of the various regions of an antibody molecule are analysed and correlated with biological function. The structural features which relate to potential applications are detailed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
591
4
11

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 850 publications
(628 citation statements)
references
References 142 publications
22
591
4
11
Order By: Relevance
“…That more stringent selection for proteolytic stability results in the selection of clones from a single CDR group suggests that CDRs are the primary site of proteolysis. This is in accordance with the general view that CDRs form flexible surface-exposed loops (Padlan 1994;Harmsen et al 2000), which is a structure that is more susceptible to proteolysis (North 1989). However, the newly selected clones still varied considerably in proteolytic stability.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…That more stringent selection for proteolytic stability results in the selection of clones from a single CDR group suggests that CDRs are the primary site of proteolysis. This is in accordance with the general view that CDRs form flexible surface-exposed loops (Padlan 1994;Harmsen et al 2000), which is a structure that is more susceptible to proteolysis (North 1989). However, the newly selected clones still varied considerably in proteolytic stability.…”
Section: Discussionsupporting
confidence: 90%
“…A scattered pattern of amino acid substitutions is commonly found in recombinant antibodies selected for improved affinity or physicochemical stability (Daugherty et al 2000;Jermutus et al 2001;Zahnd et al 2004). It has been reported that amino acid substitutions outside the CDRs that result in increased affinity can stabilize CDR loops in a conformation that is more suitable for antigen binding (Foote and Winter 1992;Padlan 1994;Wedemayer et al 1997). Possibly, the higher proteolytic stability of the newly selected VHHs is similarly caused by reduced flexibility of CDR loops.…”
Section: Discussionmentioning
confidence: 99%
“…In one, the four different isotypes provide different combinations of V L CDR1 and CDR2 length which influence the binding site topology, probably by specific support of V H CDR3; those V L with longer CDR2 such as r associated with V H having short CDR3 [36]. This hypothesis would predict that V H genes expressed at different stages of development or in different tissues would show an L chain preference.…”
Section: Discussion Natural History Of Four Ancient Igl Cladesmentioning
confidence: 99%
“…Imprecision in gene segment joining and variation in the extent of N nucleotide insertion create a CDR-H3 repertoire that ranges from unmodified and intact germ-lineencoded sequence to sequences where extensive nibbling and N addition have obscured the identity of the D H progenitor. The broad range of diversity available to CDR-H3 has functional consequences, because its location at the center of the antigen binding site, as classically defined, permits this interval to often play a significant role in antigen recognition and binding [3][4][5].…”
Section: Introductionmentioning
confidence: 99%